Karakteristik Medan Magnet Pada Kumparan Berinti Besi Sebagai Bahan Pembuatan Prototipe Kereta Maglev - Jamaludin, Jamaludin; Pradipta, Andri (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2019)
The working principle of the Maglev train is the interaction between the magnetic poles contained in the train with the magnetic poles that are along the train track. The magnetic poles are made of coils with superconducting wires that are electrified. In theory the magnitude of the magnetic field depends on the amount of current flowing, the core of the coil and the number of turns. In this research, a coil with an iron core of 5 cm in length and 8mm in diameter has 400 turns. Characteristic testing is done by directing the electric current in the coil by varying the amount of current. Measurement of the magnetic field is carried out at a certain distance between 0 to 5 cm with a range of 0.5 cm from the end of the coil. The largest magnetic field is produced at the closest distance to the coil and the smallest is at the farthest distance from the coil that is not affected by the magnetic field. The farthest distance that is still affected by the magnetic field is between 25 to 40 cm